Evidence for subsurface ordering of oxygen vacancies on the reduced CeO2 (111) surface using density-functional and statistical calculations - Murgida, Gustavo Ezequiel; Ganduglia Pirovano, Maria Veronica (American Physical Society, 2013)
Fil: Murgida, Gustavo Ezequiel. Comisión Nacional de Energía Atómica. Gerencia del Área de Investigaciones y Aplicaciones no Nucleares. Gerencia de Física (Centro Atómico Constituyentes); Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina